WO3-based photocatalysts: morphology control, activity enhancement and multifunctional applications - Dong, Pengyu; Hou, Guihua; Xi, Xinguo; Shao, Rong; Dong, Fan (Environmental science. Nano, 2017)
WO 3 , a visible-light responsive photocatalyst, absorbs light up to 480 nm with several intriguing advantages such as low cost, harmlessness, and stability in acidic and oxidative conditions. In this review, the relationship between the morphology control and the photocatalytic activity of WO 3 is analyzed in detail. In particular, the WO 3 exposed {002}-dominant facet with high-surface-energy generally shows excellent photocatalytic performance, and the quantum-confined WO 3 nanoparticles exhibit a promising future. Furthermore, some main strategies for improving the photocatalytic activity of WO 3 , such as surface hybridization with graphene, noble metal deposition, semiconductor coupling, and alkali hydroxide loading, are systematically summarized and highlighted. In the noble metal/WO 3 composite, the noble metal always works as an electron pool and catalyzes O 2 reduction through a multi-electron reduction process to form H 2 O 2 and H 2 O instead of the traditional single-electron process. In addition, the preparation methods, photocatalytic enhancement factors and possible photocatalytic mechanisms for the WO 3 /semiconductor composites are described. Moreover, various photocatalytic applications of WO 3 -based photocatalysts, such as photodegradation of organics, air purification, self-cleaning, CO 2 photoreduction, heavy metal ion treatment, hydrogen evolution from splitting water, and bacterial disinfection, are introduced and summarized. Finally, the main conclusions and future perspectives of WO 3 -based photocatalysts are pointed out. It is anticipated that this review could offer guidelines for designing novel WO 3 -based photocatalysts with low cost and high efficiency, which can possess promising prospects of application to meet the urgent demands of highly efficient solar energy conversion in the areas of renewable energy and environmental purification. This review focuses on the morphology control, enhancement strategies of photocatalytic activity and applications of WO 3 -based photocatalysts.